Intellectual property rights and trade: The exceptional case of GMOs. (27th October 2021) - Smith, Pamela; Kong, Xiangwen
Abstract: This paper examines how foreign intellectual property rights (IPRs) affect US bilateral exports of genetically modified crops (GMOs). We apply the structural gravity model to examine GMO trade between the United States and the countries that comprise the rest of the world. Our econometric method includes the Poisson Pseudo Maximum Likelihood estimator. We use panel data including measures of countries' IPR regimes, plant patentability, plant variety rights, GMO regulations and asynchronous approvals of GMOs. Results show the United States tends to export fewer GMO crops to countries with strong IPR regimes, plant patentability and plant variety rights. These results are consistent with the market power effect, where the United States restricts exports to countries with strong protections to extract monopoly prices. Second, enforcement of IPRs strengthens the market power effect. Third, the market power effect is strong alongside with GMO regulations and asynchronous approvals. Fourth, the market power effect is larger for self‐pollinating crops vs. hybrids. These findings are robust across a variety of specifications. However, we also find a price premium in countries with less ease of US market access, with more domestic production of GMOs, and with weak traceability requirements. These features play a stronger role than IPRs in determining price.